Diaphragm coating material and preparation method thereof, lithium ion battery diaphragm and lithium ion battery

By preparing aminosilane-modified zirconium-based metal organic framework and lithiated carbon nanotube composite coating on the lithium-ion battery separator, the problems of gas accumulation and high internal resistance in lithium-ion batteries are solved, and the cycle stability of the battery is improved and Electrochemical properties.

CN119153890AInactive Publication Date: 2024-12-17华鼎国联动力电池有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411211998.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In actual applications, lithium-ion batteries have problems such as gas accumulation leading to battery volume expansion, impedance increase and electrical performance decay. The main reasons include moisture impact, short circuit phenomenon and overcharge impact, which lead to safety and performance impact.

Method used

Zirconium-based metal organic framework material was prepared by coordination method using zirconium salt and biphthalic acid, and then solvothermal modification with aminosilane compounds, and diaphragm coating material was prepared by ultrasonic mixing with lithiated carbon nanotubes. This was attached to the lithium-ion battery separator by spraying, forming an aminosilane-modified zirconium-based metal organic framework and a composite coating of lithiated carbon nanotubes.

Benefits of technology

The composite coating material can effectively absorb moisture and gas, reduce battery gas release, reduce internal resistance, and significantly improve the cycle stability and electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153890A_ABST
    Figure CN119153890A_ABST
Patent Text Reader

Abstract

The invention relates to a diaphragm coating material and a preparation method thereof, a lithium ion battery diaphragm and a lithium ion battery, and relates to the technical field of lithium ion batteries, the preparation method comprises the following steps: taking zircon salt and biphenyldicarboxylic acid as raw materials, and preparing a zirconium-based metal organic framework material through a coordination method; preparing an amino silane modified zirconium-based metal organic framework material by taking the zirconium-based metal organic framework material and an amino silane compound as raw materials through a solvothermal method; the amino silane modified zirconium-based metal organic framework material and lithiated carbon nanotubes are used as raw materials, and the diaphragm coating material is prepared through an ultrasonic mixing method. The diaphragm coating material is prepared through a coordination method, a solvothermal method, an ultrasonic mixing method and the like in sequence, and is uniformly attached to the battery diaphragm to serve as a coating of the lithium ion battery diaphragm, so that the problems of moisture, gas production, high internal resistance, poor cycle performance and the like in a lithium ion battery are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a diaphragm coating material and a preparation method thereof, a lithium ion battery diaphragm, and a lithium ion battery. Background Art

[0002] As the core energy storage solution for today's electric vehicles, portable electronic devices and renewable energy storage systems, the performance, safety and reliability of lithium-ion batteries are directly affected by the progress of diaphragm technology. As a key component between the positive and negative electrodes, the diaphragm not only needs to prevent battery short circuits, but also needs to ensure the free migration of lithium ions during charging and discharging. Traditionally, polypropylene and polyethylene are widely used as diaphragm materials due to their excellent mechanical strength and electrochemical stability. However, in the face of the demand for high energy density and fast charging, researchers have begun to explore more innovative materials and technologies.

[0003] As a new type of diaphragm, ceramic coating membrane significantly improves the thermal stability of the diaphragm and enhances its flame retardant properties by coating ceramic particles on a polymer substrate, which is crucial for preventing thermal runaway of batteries in high temperature environments. In addition, the application of nanofiber membrane technology uses nano-scale fiber materials to achieve a higher specific surface area, thereby promoting faster conduction of lithium ions and improving the rapid charging and discharging capabilities and cycle life of the battery.

[0004] Although new diaphragm materials have shown significant advantages in performance, their production costs and technical maturity are still urgent issues to be resolved. For large-scale applications, reducing costs and improving manufacturing efficiency are the key to the development of the industry. Therefore, the research and development of composite materials has become a focus of attention. By combining the advantages of different materials, a composite diaphragm with high conductivity, good mechanical strength and thermal stability is developed to effectively meet the needs of various applications.

[0005] However, lithium-ion batteries still have some obvious shortcomings in practical applications, such as gas accumulation leading to battery volume expansion, impedance increase, and electrical performance degradation. Combining the data of the three-electrode data monitoring of the charging and discharging process of lithium iron phosphate (LFP) lithium soft-pack batteries, it can be found that the main causes of bloating include:

[0006] Effect of moisture: Although trace amounts of moisture in lithium batteries contribute to the stability of the solid electrolyte interface film (SEI film), excess moisture will consume lithium salts and produce corrosive hydrogen fluoride, resulting in decreased capacity and increased safety hazards.

[0007] Short circuit phenomenon: When a short circuit point appears inside a lithium battery, the local temperature rises sharply, causing the electrolyte to decompose and the carbon dioxide content in the gas component of the flatulent battery to increase significantly.

[0008] Impact of overcharging: In the early stage of overcharging, the lithium element of the positive electrode is not completely transferred, the oxidizability is low, and a small amount of carbon dioxide and olefins are produced. As the overcharging process proceeds, the decomposition of lithium compounds and the accumulation of lithium dendrites at the negative electrode intensify the oxidation reaction, produce more carbon dioxide gas and cause the internal pressure to rise, causing the aluminum-plastic film of the flexible packaging to expand.

[0009] Sealing and SEI membrane influence: Insufficient sealing of the battery will allow moisture from the air to penetrate, increasing the generation of carbon dioxide. At the same time, if the SEI membrane is not dense enough, it will allow electrons to penetrate, causing the electrolyte solvent to react with the membrane to generate a large number of free radicals and release gas. These factors will have a combined impact on the safety and performance of the battery. Summary of the invention

[0010] In order to solve the above problems, the present invention provides a diaphragm coating material and a preparation method thereof, a lithium ion battery diaphragm, and a lithium ion battery.

[0011] In a first aspect, the present invention provides a method for preparing a membrane coating material, the preparation method comprising the following steps:

[0012] Using zirconium salt and biphenyl dicarboxylic acid as raw materials, zirconium-based metal organic framework materials were prepared by coordination method;

[0013] Using the zirconium-based metal organic framework material and aminosilane compounds as raw materials, preparing an aminosilane-modified zirconium-based metal organic framework material by a solvothermal method;

[0014] The aminosilane-modified zirconium-based metal organic framework material and lithiated carbon nanotubes are used as raw materials to prepare a diaphragm coating material through an ultrasonic mixing method.

[0015] Furthermore, the steps of preparing a zirconium-based metal organic framework material by a coordination method using zirconium salt and biphenyl dicarboxylic acid as raw materials include the following process:

[0016] Mixing zirconium salt, N,N-dimethylformamide and hydrochloric acid having a concentration of 12 to 14 mol / L to obtain solution 1;

[0017] Mixing biphenyl dicarboxylic acid and N,N-dimethylformamide to obtain solution 2;

[0018] The solution 1 and the solution 2 are mixed, and then stirred at 100 to 120° C. for 12 to 15 hours to obtain the zirconium-based metal organic framework material.

[0019] Furthermore, the molar ratio of the zirconium salt to the biphenyl dicarboxylic acid is (2-4):(3-5), and the zirconium salt includes zirconium chloride.

[0020] Furthermore, the step of preparing an aminosilane-modified zirconium-based metal organic framework material by a solvothermal method using the zirconium-based metal organic framework material and an aminosilane compound as raw materials comprises the following process:

[0021] The zirconium-based metal organic framework material is added to toluene and stirred at 100 to 120° C. for 1 to 2 hours to obtain a mixture, and then an aminosilane compound is added to react for 24 to 28 hours to obtain a mixture;

[0022] The mixture is filtered, and then the obtained solid is washed with ethanol and dried to obtain the aminosilane-modified zirconium-based metal organic framework material.

[0023] Furthermore, the weight molar ratio of the zirconium-containing metal organic framework material to the aminosilane compound is (50-60 mg): (0.5-10 mmol); the aminosilane compound includes 3-aminopropyltriethoxysilane.

[0024] Furthermore, the step of preparing the diaphragm coating material by ultrasonic mixing using the aminosilane-modified zirconium-based metal organic framework material and lithiated carbon nanotubes as raw materials includes the following process:

[0025] The aminosilane-modified zirconium-based metal organic framework material and the lithiated carbon nanotubes are added to dimethylformamide for ultrasonic mixing for 30 to 60 minutes, followed by stirring for 5 to 10 hours to obtain the diaphragm coating material;

[0026] Wherein, the weight ratio of the aminosilane-modified zirconium-based metal organic framework material and the lithiated carbon nanotube is (1-1):(5-1); the weight volume ratio of the aminosilane-modified zirconium-based metal organic framework material and the dimethylformamide is (20-40 mg):(30-60 mL);

[0027] The method for preparing lithiated carbon nanotubes comprises the following process: casting molten lithium onto carbon nanotubes, and forming lithiated carbon nanotubes after cooling to room temperature; wherein the weight ratio of the lithium to the carbon nanotubes is (10-15):(40-60).

[0028] In a second aspect, the present invention provides a membrane coating material, wherein the membrane coating material is prepared by the preparation method described in any one of the first aspects.

[0029] In a third aspect, the present invention provides a lithium-ion battery separator, comprising a lithium-ion separator substrate and a coating attached to the surface of the lithium-ion separator substrate, wherein the coating is made of the separator coating material described in any one of the second aspects; the lithium-ion separator substrate comprises a polyethylene lithium-ion separator.

[0030] Furthermore, the preparation method of the lithium ion battery separator comprises the following steps:

[0031] The separator coating material is coated on the lithium ion separator substrate by spraying, and then dried to obtain the lithium ion battery separator;

[0032] Wherein, the thickness of the coating is 10-20 um.

[0033] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises at least the diaphragm coating material described in any one of the second aspect, or the lithium-ion battery comprises at least the lithium-ion battery diaphragm described in any one of the third aspect.

[0034] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0035] The embodiment of the present invention provides a diaphragm coating material and a preparation method thereof, a lithium-ion battery diaphragm, and a lithium-ion battery. The present invention provides a diaphragm coating material, which is prepared by a coordination method, a solvent thermal method, an ultrasonic mixing method, and a spraying method in sequence, and is uniformly attached to a battery diaphragm as a coating of a lithium-ion battery diaphragm, thereby solving the problems existing in lithium-ion batteries such as moisture, gas production, high internal resistance, and poor cycle performance. Specifically:

[0036] (1) Absorption of moisture and gas: The aminosilane-modified metal organic framework in the composite coating has excellent moisture and gas adsorption capacity, which can effectively capture and neutralize hydrogen fluoride, carbon dioxide, etc. in lithium-ion batteries, thereby significantly reducing the release of battery gas.

[0037] (2) Reduce internal resistance and improve cycle performance: Lithiated carbon nanotubes promote the rapid migration of electrons / ions, reduce the internal resistance of lithium-ion batteries and significantly improve the cycle stability of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0040] Figure 1 A schematic flow chart of a method for preparing a diaphragm coating material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0043] There are many technologies for preparing lithium-ion battery separator coating materials. The following are some of the commonly used methods:

[0044] Nano oxide coating: Nano oxides, such as aluminum oxide or lithium oxide, are used to form coatings through sol-gel method, atomic layer deposition and other methods. This coating can improve the thermal stability of the diaphragm and its ability to resist electrolyte extracts. Polymer coating: Polymer materials, such as polyolefins or polysulfones, are used to form coatings through solution blending, electrodeposition or thin film impregnation. This coating can improve the mechanical strength and chemical corrosion resistance of the diaphragm. Carbon nanotube coating: The conductivity and mechanical strength of carbon nanotubes are used to form a coating on the surface of the diaphragm through impregnation, spraying or spray drying. This coating can improve the conductivity and thermal stability of the diaphragm.

[0045] However, there are also some disadvantages in battery separator coating technology, such as: Preparation complexity: Some coating technologies may require complex preparation steps and equipment, such as sol-gel method, atomic layer deposition, etc. This may increase the cost and difficulty of coating preparation. Increased cost: Coatings using special materials or special preparation techniques tend to increase the manufacturing cost of battery separators. Increased membrane impedance: Certain coating materials may cause the resistance of the battery separator to increase, thereby affecting the performance and efficiency of the battery. Coating stability: Some coating materials may be unstable under long-term use or extreme conditions, resulting in membrane performance degradation or defects. At the same time, lithium-ion battery separator is one of the key components in the battery. Although it has important functions, it also has some disadvantages and challenges. The following are some of the main disadvantages of lithium-ion battery separator applications:

[0046] Limiting battery performance: The separator has an impact on the performance of the battery. The characteristics of the separator, such as conductivity, ion transport rate and thermal stability, will have a certain impact on the battery performance. Selecting an inappropriate separator material or a poorly designed separator may lead to poor battery performance. Poor conductivity: Conventional polymer separators have relatively low conductivity, so they may increase the resistance inside the battery, affecting the performance and efficiency of the battery.

[0047] The present invention provides a method for preparing a membrane coating material, such as Figure 1 As shown, the preparation method comprises the following steps:

[0048] Using zirconium salt and biphenyl dicarboxylic acid as raw materials, zirconium-based metal organic framework materials were prepared by coordination method;

[0049] Using the zirconium-based metal organic framework material and aminosilane compounds as raw materials, preparing an aminosilane-modified zirconium-based metal organic framework material by a solvothermal method;

[0050] The aminosilane-modified zirconium-based metal organic framework material and lithiated carbon nanotubes are used as raw materials to prepare a diaphragm coating material through an ultrasonic mixing method.

[0051] The present invention provides a diaphragm coating material, which is prepared by a coordination method, a solvent thermal method, an ultrasonic mixing method and a spraying method in sequence, and is uniformly attached to a battery diaphragm as a coating of a lithium-ion battery diaphragm, thereby solving the problems existing in lithium-ion batteries such as moisture, gas production, high internal resistance, and poor cycle performance. Specifically:

[0052] (1) Absorption of moisture and gas: The aminosilane-modified metal organic framework in the composite coating has excellent moisture and gas adsorption capacity, which can effectively capture and neutralize hydrogen fluoride, carbon dioxide, etc. in lithium-ion batteries, thereby significantly reducing the release of battery gas.

[0053] (2) Reduce internal resistance and improve cycle performance: Lithiated carbon nanotubes promote the rapid migration of electrons / ions, reduce the internal resistance of lithium-ion batteries and significantly improve the cycle stability of lithium-ion batteries.

[0054] In some specific embodiments, the present invention prepares a membrane coating material and a lithium-ion battery membrane through the following steps.

[0055] (1) Preparation of Zr-based metal organic framework products by coordination method. Take 2-4 mmol of zirconium chloride (ZrCl4) in a beaker, add 30-40 mL of N,N-dimethylformamide (DMF) and 3-4 mL of hydrochloric acid (HCl) with a concentration of 12-14 mol / L, mix and stir for 20-30 min, and call it solution 1. Then, take 3-5 mmol of biphenyl dicarboxylic acid (C 14 H10 O4) in a beaker, slowly add 40-50 mL DMF and stir for 30-40 min, which is called solution 2. Mix solution 1 and solution 2 evenly, and stir at 100-120°C for 12-15 h to obtain a Zr-based metal organic framework product (UiO-67).

[0056] (2) Preparation of aminosilane-modified Zr-based metal organic framework product by solvothermal method. Take 50-60 mg of UiO-67 powder in a beaker, add 70-80 mL of toluene (C7H8) solvent and stir at 100-120°C for 1-2 hours. Then, add 0.5-10 mmol of 3-aminopropyltriethoxysilane (abbreviated as: 3AS) dropwise into the mixture and react for 24-28 hours. Then, filter the reaction mixture through nylon and wash it three times with ethanol to remove unreacted aminosilane. Finally, dry it in a vacuum drying oven at 100-120°C for 24-48 hours to obtain the aminosilane-modified Zr-based metal organic framework product (UiO-67-3AS).

[0057] (3) Preparation of aminosilane modified metal organic framework and lithiated carbon nanotube composite coating material by ultrasonic mixing method. Take 40-60 mg of carbon nanotubes in a porcelain boat, melt 10-15 mg of lithium at 200-350 ° C, cast the molten lithium onto the carbon nanotubes, and after cooling to room temperature, form lithiated carbon nanotubes (CNT-Li). Disperse 20-40 mg of UiO-67-3AS material in 30-60 mL of dimethylformamide (DMF), and disperse CNT-Li evenly by ultrasonic treatment for 30-60 min. Mix the obtained UiO-67-3AS with the CNT-Li solution and stir for 5-10 h to form a mixed and uniformly dispersed solution, namely, aminosilane modified metal organic framework and lithiated carbon nanotube composite coating material.

[0058] (4) Spraying method for preparing lithium-ion battery separator coating. The mixed aminosilane-modified metal organic framework and lithiated carbon nanotube composite coating material is evenly coated on the lithium-ion separator polyethylene (PE) by spraying. The coated lithium-ion separator is dried to remove the solvent. The separator is baked at a temperature of 30 to 45°C to allow the aminosilane-modified metal organic framework and lithiated carbon nanotube composite coating material to adhere to the separator to form a stable coating.

[0059] It should be noted that: (1) In the present technical solution, the metal source can be one of zirconium chloride, zinc chloride, cobalt chloride, manganese chloride and cerium chloride. (2) In the present technical solution, the lithiated carbon nanotubes can be one of metal carbides (MXene), graphene, carbon nanotubes and conductive polymers. (3) In the present technical solution, the ultrasonic stirring method can be one of magnetic stirring, vortex stirring, bubble stirring and centrifugal stirring. (4) In the present technical solution, the spraying method can be one of solution coating, ion exchange membrane method, plasma and the like.

[0060] The present invention can prepare a diaphragm coating material for solving gas generation by the above method, and the main problems solved are as follows.

[0061] In this way, the aminosilane-modified metal organic framework and the lithiated carbon nanotube composite coating material are attached to the diaphragm to form a stable coating. The main advantage is that the aminosilane-modified metal organic framework and the lithiated carbon nanotube composite coating material are attached to the diaphragm to form a stable coating and are combined with each other to prepare a new type of diaphragm coating. The aminosilane-modified metal organic framework is highly porous and chemically stable, has a high absorption capacity for gas and water, and can well solve the flatulence problem in lithium-ion battery applications. And the amino functional group therein can improve ionic conductivity. The lithiated carbon nanotube conductive skeleton can promote the rapid migration of electrons / ions, reduce the internal resistance of lithium-ion batteries and improve the cycle stability of lithium-ion batteries.

[0062] The present invention provides a lithium ion battery, wherein the lithium ion battery comprises at least the diaphragm coating material described in any one of the second aspects, or the lithium ion battery comprises at least the lithium ion battery diaphragm described in any one of the third aspects.

[0063] Accordingly, a method for preparing a lithium ion battery as described below comprises the following steps:

[0064] S1': preparing positive and negative electrode slurries for lithium-ion batteries respectively, wherein the slurry components include positive and negative electrode materials, a binder, a thickener and a conductive agent.

[0065] Preferably, in the lithium-ion battery positive electrode slurry composition, the positive electrode material is lithium iron phosphate positive electrode material, the adhesive is polyvinylidene fluoride, and the conductive agent is conductive carbon black.

[0066] Preferably, in the negative electrode slurry composition of the lithium ion battery, the binder is styrene-butadiene rubber, the thickener is sodium carboxymethyl cellulose, the negative electrode material is graphite, and the conductive agent is conductive carbon black.

[0067] S2': A positive electrode and a negative electrode of a lithium-ion battery, which are prepared by coating the positive and negative electrode slurries on the positive electrode and negative electrode current collectors respectively.

[0068] Preferably, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0069] Preferably, the method for preparing the positive and negative electrode sheets of a lithium-ion battery comprises coating the positive and negative electrode slurries on the positive and negative electrode current collectors respectively, and performing rolling, slitting, die-cutting and baking to prepare the sheets.

[0070] S3': A lithium-ion battery, which is produced by laminating, packaging, injecting, wetting, forming, degassing, aging, capacity testing and sorting the positive and negative electrodes of the lithium-ion battery.

[0071] Preferably, the lithium-ion battery comprises an electrolyte, a separator, a shell, and a positive electrode and a negative electrode of the lithium-ion battery.

[0072] Preferably, the positive electrode and negative electrode of the lithium ion battery are separated by a diaphragm, and the electrolyte diaphragm and the positive electrode and negative electrode of the lithium ion battery are located inside the shell. The coating on the diaphragm is the above-prepared aminosilane modified metal organic framework and lithiated carbon nanotube composite coating material.

[0073] Preferably, the lithium-ion battery is a three-electrode soft pack, a square soft pack or a square shell.

[0074] It should be noted that the membrane coating material and preparation method thereof, lithium-ion battery membrane, and component raw materials involved in the lithium-ion battery provided in the embodiments of the present invention, unless otherwise specified or specified, can directly adopt commercially available products or be prepared by existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of lithium-ion batteries or directly carried out using existing equipment, and the present invention document will not describe them one by one.

[0075] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0076] Example 1

[0077] This example provides a diaphragm coating material that can solve the problem of flatulence in lithium-ion batteries, reduce the internal resistance of batteries, and improve the cycle performance, and further applies it to prepare lithium-ion battery diaphragms and lithium-ion batteries, specifically including the following processes:

[0078] (1) Take 3 mmol of zirconium chloride (ZrCl4) in a beaker, add 35 mL of N,N-dimethylformamide (DMF) and 3.5 mL of 13 mol / L hydrochloric acid (HCl), mix and stir for 25 min, and call it solution 1. Then, take 4 mmol of biphenyl dicarboxylic acid (C 14 H 10 O4) in a beaker, 45 mL of DMF was slowly added thereto and stirred for 35 min, which was called solution 2. Solution 1 and solution 2 were mixed evenly, and stirred at 110° C. for 13.5 h to obtain a Zr-based metal organic framework product (UiO-67).

[0079] Secondly, 55mg UiO-67 powder was placed in a beaker, 75mL toluene (C7H8) solvent was added and stirred at 110℃ for 1.5h. Then, 5.5mmol 3-aminopropyltriethoxysilane (abbreviated as: 3AS) was added dropwise to the mixture and reacted for 26h. The reaction mixture was filtered through nylon and washed three times with ethanol to remove unreacted aminosilane. Finally, the product was dried at 110℃ in a vacuum drying oven for 26h to obtain an aminosilane-modified Zr-based metal organic framework product (UiO-67-3AS). Then, 50mg carbon nanotubes were placed in a porcelain boat, 12.5mg lithium was melted at 250℃, and the molten lithium was cast on the carbon nanotubes. After cooling to room temperature, lithiated carbon nanotubes (CNT-Li) were formed.

[0080] Finally, 30 mg of UiO-67-3AS material was dispersed in 40 mL of dimethylformamide (DMF), and CNT-Li (added in an amount of 10 mg) was evenly dispersed by ultrasonic treatment for 40 min. The obtained UiO-67-3AS was mixed with the CNT-Li solution and stirred for 5 h to form a mixed and uniformly dispersed solution (i.e., a diaphragm coating material was obtained). Finally, the mixed solution was evenly coated on the lithium ion diaphragm polyethylene (PE) by spraying. The coated lithium ion diaphragm was dried to remove the solvent. The diaphragm was baked at 30 ° C so that UiO-67-3AS and CNT-Li adhered to the diaphragm to form a stable coating with a thickness of 15 um, i.e., a lithium ion battery diaphragm was obtained.

[0081] (2) Dissolve 100g of polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solvent, and then add lithium iron phosphate (LiFePO4) positive electrode material and conductive agent conductive carbon black and mix them evenly. Among them, the lithium-ion battery positive electrode slurry is LiFePO4 (97%), PVDF (1.5%) and conductive agent (1.5%) according to weight percentage. Dissolve 150g of sodium carboxymethyl cellulose (CMC) in deionized water, and then add negative electrode material graphite, conductive agent graphene-loaded lithium carbon nanotubes, and styrene-butadiene rubber (SBR) and mix them evenly. Among them, the lithium-ion battery negative electrode slurry is graphite negative electrode material (95.5%), conductive agent conductive carbon black (1.5%), CMC (1.5%) and SBR (1.5%) according to weight percentage.

[0082] (3) The obtained positive electrode slurry of lithium-ion battery is coated on the aluminum foil current collector, and the negative electrode slurry is coated on the copper foil current collector. Finally, the positive and negative electrode sheets are produced by rolling, slitting, die-cutting and baking.

[0083] (4) Assemble the positive and negative electrode sheets in step (3) with a separator, an electrolyte and a shell into a lithium-ion battery. The separator is polyethylene (PE), and the coating of the separator is UiO-67-3AS and CNT-Li attached to the separator to form a stable coating.

[0084] Example 2

[0085] This example provides a diaphragm coating material that solves the problem of flatulence in lithium-ion batteries, reduces the internal resistance of batteries, and improves the cycle performance, and is further used to prepare lithium-ion battery diaphragms and lithium-ion batteries. The only difference from Example 1 is that the conditions and parameters in the preparation method of the diaphragm coating material are different; the preparation method of the diaphragm coating material includes the following process:

[0086] (1) Take 2 mmol of zirconium chloride (ZrCl4) and add 30 mL of N,N-dimethylformamide (DMF) and 3 mL of 12 mol / L hydrochloric acid (HCl) in a beaker and stir for 20 min. This is called solution 1. Next, take 3 mmol of biphenyl dicarboxylic acid (C 14 H 10 O4) in a beaker, 40 mL of DMF was slowly added thereto and stirred for 30 min, which was called solution 2. Solution 1 and solution 2 were mixed evenly, and stirred at 100° C. for 12 h to obtain a Zr-based metal organic framework product (UiO-67).

[0087] Secondly, 50mgUiO-67 powder was placed in a beaker, 70mL of toluene (C7H8) solvent was added and stirred at 100℃ for 1h. Then, 0.5mmol of 3-aminopropyltriethoxysilane (abbreviated as: 3AS) was added dropwise to the mixture and reacted for 24h. The reaction mixture was filtered through nylon and washed three times with ethanol to remove unreacted aminosilane. Finally, the product (UiO-67-3AS) was obtained by drying at 100℃ in a vacuum drying oven for 24h. Then, 40mg of carbon nanotubes were placed in a porcelain boat, 10mg of lithium was melted at 200℃, and the molten lithium was cast on the carbon nanotubes. After cooling to room temperature, lithiated carbon nanotubes (CNT-Li) were formed.

[0088] Finally, 20 mg of UiO-67-3AS material was dispersed in 30 mL of dimethylformamide (DMF), and CNT-Li (added in an amount of 5 mg) was evenly dispersed by ultrasonic treatment for 30 min. The obtained UiO-67-3AS and CNT-Li solutions were mixed and stirred for 5 h to form a mixed and uniformly dispersed solution (i.e., a diaphragm coating material was obtained).

[0089] Example 3

[0090] This example provides a diaphragm coating material that solves the problem of flatulence in lithium-ion batteries, reduces the internal resistance of batteries, and improves the cycle performance, and is further used to prepare lithium-ion battery diaphragms and lithium-ion batteries. The only difference from Example 1 is that the conditions and parameters in the preparation method of the diaphragm coating material are different; the preparation method of the diaphragm coating material includes the following process:

[0091] (1) Take 4 mmol of zirconium chloride (ZrCl4) and add 40 mL of N,N-dimethylformamide (DMF) and 4 mL of 14 mol / L hydrochloric acid (HCl) in a beaker and stir for 30 min. This is called solution 1. Next, take 5 mmol of biphenyl dicarboxylic acid (C 14 H 10 O4) in a beaker, 50 mL of DMF was slowly added thereto and stirred for 40 min, which was called solution 2. Solution 1 and solution 2 were mixed evenly, and stirred at 120° C. for 15 h to obtain a Zr-based metal organic framework product (UiO-67).

[0092] Secondly, 60mg UiO-67 powder was placed in a beaker, 80mL toluene (C7H8) solvent was added and stirred at 120℃ for 2h. Then, 10mmol 3-aminopropyltriethoxysilane (abbreviated as: 3AS) was added dropwise to the mixture and reacted for 28h. The reaction mixture was filtered through nylon and washed three times with ethanol to remove unreacted aminosilane. Finally, the mixture was dried at 120℃ in a vacuum oven for 48h to obtain an aminosilane-modified Zr-based metal organic framework product (UiO-67-3AS). Then, 60mg carbon nanotubes were placed in a porcelain boat, 15mg lithium was melted at 350℃, the molten lithium was cast on the carbon nanotubes, and after cooling to room temperature, lithiated carbon nanotubes (CNT-Li) were formed.

[0093] Finally, 40 mg of UiO-67-3AS material was dispersed in 60 mL of dimethylformamide (DMF), and CNT-Li (added in an amount of 15 mg) was evenly dispersed by ultrasonic treatment for 60 min. The obtained UiO-67-3AS and CNT-Li solutions were mixed and stirred for 10 h to form a mixed and uniformly dispersed solution (i.e., a diaphragm coating material was obtained).

[0094] Comparative Example 1

[0095] This example provides a membrane coating material, which is further used to prepare lithium-ion battery membranes and lithium-ion batteries. The only difference from Example 1 is that the membrane coating material uses the aminosilane-modified Zr-based metal organic framework product (UiO-67-3AS) obtained in Example 1.

[0096] Comparative Example 2

[0097] This example provides a membrane coating material, which is further used to prepare lithium-ion battery membranes and lithium-ion batteries. The only difference from Example 1 is that the membrane coating material uses the lithiated carbon nanotubes (CNT-Li) obtained in Example 1.

[0098] Comparative Example 3

[0099] This example provides a lithium-ion battery, which is different from Example 1 only in that the lithium-ion battery separator in the lithium-ion battery is only polyethylene (there is no separator coating material on the polyethylene).

[0100] Comparative Example 4

[0101] This example provides a lithium-ion battery, which is different from Example 1 only in that the lithium-ion battery separator in the lithium-ion battery is only polypropylene (there is no separator coating material on the polypropylene).

[0102] Test Case

[0103] In this example, the lithium-ion batteries obtained from the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests. The comparison of the change in cell thickness, gas production, internal resistance of the lithium-ion battery and room temperature cycle retention rate before and after the test is shown in Table 1.

[0104] Table 1

[0105] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Cell thickness change after test (mm) 0.1 0.2 0.28 0.3 0.5 3.0 3.2 Lithium-ion battery gas production (mL) 0.8 1.5 1.7 2.1 5.2 10.3 11.5 Lithium-ion battery internal resistance (mΩ) 0.45 0.68 0.74 0.87 0.95 1.03 1.14 1000 cycles at room temperature retention rate (%) 97 90 89 87 85 81 78

[0106] As can be seen from Table 1, the lithium-ion battery separator coating material of Example 1 has good properties. Mainly manifested in the change in cell thickness before and after the test, the gas production of the lithium-ion battery, the internal resistance of the lithium-ion battery and the room temperature cycle retention rate, the performance of several test items are all higher than those of Comparative Examples 1 to 4. It shows that the aminosilane-modified metal organic framework is highly porous and chemically stable, has a high absorption capacity for gas and water, can well solve the flatulence problem in the application of lithium-ion batteries, and the amino functional groups therein can improve the ionic conductivity. The lithiated carbon nanotube conductive skeleton can promote the rapid migration of electrons / ions, reduce the internal resistance of lithium-ion batteries and improve the cycle stability of lithium-ion batteries.

[0107] In summary, the present invention proposes an innovative solution to the gas production problem in practical lithium-ion batteries. The present invention prepares a composite coating material of an aminosilane-modified metal organic framework and lithiated carbon nanotubes by coordination method, solvothermal method, ultrasonic mixing method and spraying method, and uniformly attaches it to the battery separator. The aminosilane-modified metal organic framework in the composite coating has excellent gas adsorption capacity and can effectively capture and neutralize hydrogen fluoride, carbon dioxide, etc. in lithium-ion batteries, thereby significantly reducing the release of battery gas. Lithiated carbon nanotubes promote the rapid migration of electrons / ions, reduce the internal resistance of lithium-ion batteries and improve the cycle stability of lithium-ion batteries. By performing this surface modification on the separator, not only the chemical stability of the battery is improved, but also the service life of the battery is extended. The implementation of this technology will provide strong support for the further development of lithium-ion batteries in terms of high performance and safety, and also provide a reference for the safety improvement of other related electrochemical energy storage devices.

[0108] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0109] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a diaphragm coating material, characterized in that: The preparation method comprises the following steps: Using zirconium salt and biphenyl dicarboxylic acid as raw materials, zirconium-based metal organic framework materials were prepared by coordination method; Using the zirconium-based metal organic framework material and aminosilane compounds as raw materials, preparing an aminosilane-modified zirconium-based metal organic framework material by a solvothermal method; The aminosilane-modified zirconium-based metal organic framework material and lithiated carbon nanotubes are used as raw materials to prepare a diaphragm coating material through an ultrasonic mixing method.

2. The method for preparing a diaphragm coating material according to claim 1, characterized in that: The steps of preparing zirconium-based metal organic framework materials by coordination method using zirconium salt and biphenyl dicarboxylic acid as raw materials include the following processes: Mixing zirconium salt, N,N-dimethylformamide and hydrochloric acid having a concentration of 12 to 14 mol / L to obtain solution 1; Mixing biphenyl dicarboxylic acid and N,N-dimethylformamide to obtain solution 2; The solution 1 and the solution 2 are mixed, and then stirred at 100 to 120° C. for 12 to 15 hours to obtain the zirconium-based metal organic framework material.

3. The method for preparing the diaphragm coating material according to claim 2, characterized in that: The molar ratio of the zirconium salt to the biphenyl dicarboxylic acid is (2-4):(3-5), and the zirconium salt includes zirconium chloride.

4. The method for preparing a diaphragm coating material according to claim 1, characterized in that: The step of using the zirconium-based metal organic framework material and the aminosilane compound as raw materials to prepare the aminosilane-modified zirconium-based metal organic framework material by a solvent thermal method comprises the following process: The zirconium-based metal organic framework material is added to toluene and stirred at 100 to 120° C. for 1 to 2 hours to obtain a mixture, and then an aminosilane compound is added to react for 24 to 28 hours to obtain a mixture; The mixture is filtered, and then the obtained solid is washed with ethanol and dried to obtain the aminosilane-modified zirconium-based metal organic framework material.

5. The method for preparing a diaphragm coating material according to claim 4, characterized in that: The weight molar ratio of the zirconium-based metal organic framework material and the aminosilane compound is (50-60 mg): (0.5-10 mmol); the aminosilane compound includes 3-aminopropyltriethoxysilane.

6. The method for preparing a diaphragm coating material according to claim 1, characterized in that: The steps of preparing the diaphragm coating material by ultrasonic mixing using the aminosilane-modified zirconium-based metal organic framework material and lithiated carbon nanotubes as raw materials include the following process: The aminosilane-modified zirconium-based metal organic framework material and the lithiated carbon nanotubes are added to dimethylformamide for ultrasonic mixing for 30 to 60 minutes, followed by stirring for 5 to 10 hours to obtain the diaphragm coating material; Wherein, the weight ratio of the aminosilane-modified zirconium-based metal organic framework material and the lithiated carbon nanotube is (1-1):(5-1); the weight volume ratio of the aminosilane-modified zirconium-based metal organic framework material and the dimethylformamide is (20-40 mg):(30-60 mL); The method for preparing lithiated carbon nanotubes comprises the following process: casting molten lithium onto carbon nanotubes, and forming lithiated carbon nanotubes after cooling to room temperature; wherein the weight ratio of the lithium to the carbon nanotubes is (10-15):(40-60).

7. A membrane coating material, characterized in that: The diaphragm coating material is prepared by the preparation method described in any one of claims 1 to 6.

8. A lithium ion battery separator, characterized in that: The lithium-ion battery separator comprises a lithium-ion separator substrate and a coating attached to the surface of the lithium-ion separator substrate, wherein the coating is made of the separator coating material according to claim 7; the lithium-ion separator substrate comprises a polyethylene lithium-ion separator.

9. The lithium-ion battery separator according to claim 8, characterized in that: The method for preparing the lithium ion battery separator comprises the following steps: The separator coating material is coated on the lithium ion separator substrate by spraying, and then dried to obtain the lithium ion battery separator; Wherein, the thickness of the coating is 10-20 um.

10. A lithium ion battery, characterized in that: The lithium ion battery comprises at least the separator coating material according to claim 7, or the lithium ion battery comprises at least the lithium ion battery separator according to claim 8 or 9.

Citation Information

Patent Citations

  • Diaphragm coating material, preparation method thereof and lithium ion battery

    CN117304808A

  • Novel diaphragm coating material, preparation method thereof and lithium ion battery

    CN117650339A